Implementation of folk story to improve accounting students' mastery of past tense sentences - Prihamdani, Depi; Hidayat, Soleh; Jamaludin, Ujang; Leksono, Suroso Mukti (Panicgogy International Journal, 2023)
The aims of this study were to find out: 1) the extent to which students' competence in past tense sentences, and 2) the significant effect of using folklore on students' competence in past tense sentences in semester 2 students majoring in accounting. program of the Faculty of Economics and Business, Buana Perjuangan University, Karawang. This research method is a quantitative method. Researchers collected data by using a written test. Samples were taken using a random sampling technique of 35 students. The data were then analyzed using descriptive and inferential analysis, namely the t-test formula by Arikunto. The results of this study were that the average score of students' competence in past tense sentences before using folklore was 51.5 which was categorized as "less", then after using folklore it was 72, 37 are categorized as "good". The results of testing the hypothesis show that the t-test is higher than the t-table (17 > ​​2.04), meaning that the hypothesis is accepted. The results of the study revealed that there was a significant effect of the use of folklore on student competence in past tense sentences in semester 2 students of the accounting study program, Faculty of Economics and Business, Buana Perjuangan University, Karawang.